A quantitative analysis of decision process in social groups using human trajectories - LE, Truc Viet (Institutional Knowledge at Singapore Management University, 2014)
A group's collective action is an outcome of the group's decision-making process, which may be reached by either averaging of the individual preferences or following the choices of certain members in the group. Our problem here is to decide which decision process the group has adopted given the data of the collective actions. We propose a generic statistical framework to infer the group's decision process from the spatio-temporal data of group trajectories, where each "trajectory" is a sequence of group actions. This is achieved by systematically comparing each agent type's influence on the group actions based on an array of spatio-temporal criteria. Results of those comparisons are then aggregated into a score to make inference about the group's decision process.